GAMBARAN FAKTOR-FAKTOR YANG TERKAIT DENGAN KEPADATAN KECOA DI TEMPAT PENJUALAN BAHAN PANGAN DAN MAKANAN PASAR TRADISIONAL KOTA SEMARANG - Laeli Kartika Cahyani; Sri Yuliawati; Martini Martini (Jurnal Kesehatan Masyarakat (Undip), 2018)
Grocerie and food stores at traditional market of Semarang City must be freed from vectors including cockroaches. Infestation of cockroaches may become disease transmission risk factor at traditional market. The aims of this research to describe the related factors of density cockroaches ar grocerie and food stores at traditional market of Semarang City. It is an descriptive observational research by cross sectional approach. Samples in this research were all caught cockroaches in 66 grocerie and food stores at traditional market of Semarang City. The result of this research show that there were 57,6% of store with good sanitation and  42,4% of stores with poor sanitation. The average of air temperature at stores was 30,940C and relative humidity was 58,34%. There were 45 of 66 stores did not cockroaches control effort. The higher percentage of high cockroach density was wetfood stores (26,9%), followed by grocerie stores (25%) and dryfood stores (5%). There were 20% of stores with high density of cockroaches and 80% of stores with low density of cockroaches. A total of 437 cockroaches were caugh at stores. It was found four cockroach species, of these Periplaneta americana (15,1%), Blattella germanica (80,09%), Nauphoeta cinerea (4,58%), Neostylopyga rhombifolia (0,23%). The recommendations to owner of grocerie and food stores is to always maintain sanitation and cockroaches control effort wisely  when present  cockroaches in stores.